2022
DOI: 10.1126/science.abq1274
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric intermolecular allylic C–H amination of alkenes with aliphatic amines

Abstract: Aliphatic allylic amines are found in a great variety of complex and biorelevant molecules. The direct allylic C–H amination of alkenes serves as the most straightforward method toward these motifs. However, use of widely available internal alkenes with aliphatic amines in this transformation remains a synthetic challenge. In particular, palladium catalysis faces the twin challenges of inefficient coordination of Pd(II) to internal alkenes but excessively tight and therefore inhibitory coordination of Pd(II) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 80 publications
1
50
0
Order By: Relevance
“…First, cross-hydroalkenylation of ethyl acrylate ( 1a ) with styrene ( 1b ) under photoinduced Pd-catalyzed conditions in the presence of a Brønsted acid has been examined (Table ). Optimization studies indicated the commonly employed palladium­(II) precatalyst with xantphos ligand to be the most efficient catalytic system (Table , entries 1–4) . It was found that a combination of pivalic acid and N , N -dicyclohexylmethylamine (NCy 2 Me) as a proton source and tetrabutylammonium iodide (TBAI) as an additive was crucial for achieving highly selective and efficient hydroalkenylation (entries 5–7). , Under altered conditions, the formation of notable amounts of several side products was observed .…”
Section: Resultsmentioning
confidence: 99%
“…First, cross-hydroalkenylation of ethyl acrylate ( 1a ) with styrene ( 1b ) under photoinduced Pd-catalyzed conditions in the presence of a Brønsted acid has been examined (Table ). Optimization studies indicated the commonly employed palladium­(II) precatalyst with xantphos ligand to be the most efficient catalytic system (Table , entries 1–4) . It was found that a combination of pivalic acid and N , N -dicyclohexylmethylamine (NCy 2 Me) as a proton source and tetrabutylammonium iodide (TBAI) as an additive was crucial for achieving highly selective and efficient hydroalkenylation (entries 5–7). , Under altered conditions, the formation of notable amounts of several side products was observed .…”
Section: Resultsmentioning
confidence: 99%
“…Under this more atom-economic scenario, the amination of non-prefunctionalized allylic C–H bonds greatly increases the pool of substrates. This direction has gained attention recently with the discovery of alternative mechanistic approaches in palladium catalysis ( IV ) . Nonetheless, all current π-allyl palladium approaches toward allylic amines rely on a certain chemical space, revolving around allylic electrophiles possessing a leaving group at the allylic position ( I ), a diene moiety ( II ), or an allylic C–H bond ( III , IV ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, innovations in photochemistry have revealed that open-shell species were obtainable from alkyl/aryl halides and analogs by photoinduced palladium catalysis, the concept and application of which have been established by Gevorgyan, Fu, Yu, Glorius, and others in a series of elegant reactions. In regard to Gevorgyan’s specific work of alkyl-to-alkyl radical relay Heck reaction based on an easily installable/removable Si-based auxiliary through a selective I atom/radical translocation pathway, our group has disclosed a palladium-catalyzed aryl-to-alkyl radical relay Heck reaction between amide and vinyl arenes.…”
mentioning
confidence: 99%
“…When linear substrate 10 was employed under standard conditions, only 12% yield of the desired Heck product 11 was obtained, along with the desaturated byproduct isolated in 85% yield (eq 2). Based on the precedent literature for photoinduced palladium-catalyzed alkyl Heck reactions, , the mechanism hypothetically involves a hybrid Pd/radical pathway. Therefore, a radical-trapping experiment was conducted with TEMPO, and the benzyl radical was trapped by TEMPO to give 13 , hampering the formation of the desired coupling product (eq 3).…”
mentioning
confidence: 99%